An Overview of the Dynamics of the Volcanic Paroxysmal Explosive Activity, and Related Seismicity, at Andesitic and Dacitic Volcanoes (1960–2010) - Zobin, Vyacheslav M. (Frontiers in Earth Science, 2018)
Understanding volcanic paroxysmal explosive activity requires the knowledge of many associated processes. An overview of the dynamics of paroxysmal explosive eruptions (PEEs) at andesitic and dacitic volcanoes occurring between 1960 and 2010 is presented here. This overview is based mainly on a description of the pre-eruptive and eruptive events, as well as on the related seismic measurements. The selected eruptions are grouped according to their Volcanic Explosivity Index (VEI). A first group includes three eruptions of VEI 5-6 (Mount St. Helens, 1980; El Chichón, 1982, and Pinatubo, 1991) and a second group includes three eruptions of VEI 3 (Usu volcano, 1977; Soufriere Hills Volcano (SHV), 1996, and Volcán de Colima, 2005). The PEEs of the first group have similarity in their developments that allows to propose a 5-stage scheme of their dynamics process. Between these stages are: long (more than 120 years) period of quiescence (stage 1), preliminary volcano-tectonic (VT) earthquake swarm (stage 2), period of phreatic explosions (stage 3) and then, PEE appearance (stage 4). It was shown also that the PEEs of this group during their Plinian stage “triggered” the earthquake sequences beneath the volcanic structures with the maximum magnitude of earthquakes proportional to the volume of ejecta of PEEs (stage 5). Three discussed PEEs of the second group with lower VEI developed in more individual styles, not keeping within any general scheme. Among these, one PEE (SHV) may be considered as partly following in development to the PEEs of the first group, having stages 1, 3 and 4. The PEEs of Usu volcano and of Volcán de Colima had no preliminary long-term stages of quiescence. The PEE at Usu volcano came just at the end of the preceding short swarm of VT earthquakes. At Volcán de Colima, no preceding swarm of VT occurred. This absence of any regularity in development of lower VEI eruptions may refer, among other reasons, to different conditions of opening of the magmatic conduit during these eruptions.